2007
DOI: 10.1111/j.1478-3231.2007.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II: a novel vasoactive mediator linked to chronic liver disease and portal hypertension

Abstract: Serum UII is elevated in patients with CLD, and is associated with the severity of the underlying liver disease and the degree of portal hypertension. Baseline levels can predict future complications such as refractory ascites and patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 42 publications
4
36
2
Order By: Relevance
“…The observation that basal hemodynamics and general vasopressor responsiveness are unaltered in UT knockout mice supports the suggestion that the receptor is functionally silent under basal conditions, but this may change in cardiovascular diseases (13). In addition to elevated levels in patients with heart failure, systemic hypertension, diabetes mellitus, and renal failure (14,15), increased plasma UII levels have been reported in patients with cirrhosis (16,17).…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…The observation that basal hemodynamics and general vasopressor responsiveness are unaltered in UT knockout mice supports the suggestion that the receptor is functionally silent under basal conditions, but this may change in cardiovascular diseases (13). In addition to elevated levels in patients with heart failure, systemic hypertension, diabetes mellitus, and renal failure (14,15), increased plasma UII levels have been reported in patients with cirrhosis (16,17).…”
Section: Introductionsupporting
confidence: 55%
“…Recently, several studies have shown that UII plasma levels are increased in patients with liver cirrhosis and portal hypertension (16,17). The UII plasma levels are correlated negatively with mean arterial pressure and positively with portal pressure and severity of liver disease, as assessed using the Child-Pugh score (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, UII has an inotropic effect in humans and rats [8]. Increased plasma UII concentration was observed in patients with diabetes mellitus and end-stage kidney disease [9][10][11].…”
Section: Introductionmentioning
confidence: 99%